Mechanisms underlying the mitigating action of Maxing Shigan Decoction in acute lung injury caused by influenza virus based on UPLC-HRMS analysis and network pharmacology - Hu, Jue; Ma, Xiangming; Xiao, Yufeng; Chen, Chunjing; Liu, Chang; Lu, Jun; Wang, Xiaoqi; Lu, Fangguo (Frontiers in Immunology, 2025)
IntroductionInfluenza A virus (IAV) infection is associated with high morbidity and mortality and can ultimately lead to acute lung injury (ALI). In traditional Chinese medicine, Maxing Shigan Decoction (MXSGD) can treat exogenous wind-cold, toxic heat invading the lungs, and heat-toxicity obstructing the lungs. However, the active components and underlying mechanisms of MXSGD in IAV-induced diseases remain largely unexplored. Therefore, we aimed to investigate the active constituents of MXSGD and its underlying mechanism of action in ALI.MethodsBioactive components of MXSGD in rat serum were identified using ultra-high-performance liquid chromatography and high-resolution mass spectrometry (UPLC-HRMS). Blood-absorbed MXSGD components (i.e., the constituents of MXSGD detectable in serum) in ALI were predicted through network pharmacology and molecular docking analyses. A mouse lung injury model was established using the influenza virus. The degree of lung injury, viral load in lung tissues, serum levels of inflammatory factors, gene expression levels of inflammation-related factors in lung tissue, and macrophage polarization in the lungs were then assessed.Results and discussionIn the rat serum, 242 bioactive components were identified using UPLC-HRMS. Moreover, 56 ingredients, including glycyrrhizin, amygdalin, and ephedrine, were analyzed using network pharmacology, revealing 338 ALI-related targets and 99 core proteins in the protein–protein interaction network. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were conducted for core targets, and molecular docking confirmed the binding affinity of the main identified targets with their respective blood-absorbed components. Validation results demonstrated that MXSGD significantly ameliorated lung injury, mitigated lung congestion and inflammation, lowered viral load in mouse lung tissue, promoted macrophage polarization, and downregulated the expression of the PI3K/AKT pathway in IAV-infected mice. Overall, this study revealed the mechanisms and active ingredients underlying the therapeutic effects, highlighting of MXSGD its potential in treating IAV-induced ALI and regulating the polarization of macrophages.